EFEKTIVITAS PELAKSANAAN PROSES PEMBELAJARAN ILMU PENGETAHUAN SOSIAL - Herman man man (Jurnal Ilmu Pengetahuan Sosial, 2013)
This study aims to determine (1) The effectiveness of the implementation of the learning process in Junior High School IPS 2 Sungguminasa, (2) factors that support and hinder the implementation of the process of learning social studies, and (3) efforts that can be done to improve the effectiveness of the learning process IPS in SMP Negeri 2 Somba Opu Sungguminasa District of Gowa.The method used is quantitative descriptive , this study population was all students in Junior High School 2 Sungguminasa which amounts to 1268 and social studies teachers who were 3 people. The sample was 94 respondents consisting of 91 students and 3 teachers IPS. Samples were taken using a random sample (random sampling). The technique used in this study to collect data that observation, questionnaires, interviews and documentation . While the techniques of data analysis done by mempersentasekan each option and then to describe the meaning of the results contained these percentages .The results of this study show that (1) Implementation of the learning process in the category IPS effective in terms of all aspects of planning, implementation and evaluation aspects aspects. (2) the effectiveness of the implementation of the learning process is supported by several factors: students, curriculum, teachers and teaching materials. Inhibiting factors: media / learning tools and subject matter are still limited, (3) the efforts made to improve the effectiveness of the learning process in Junior High School IPS 2 Sungguminasa namely: providing learning preparation; provide a proper and sufficient learning; preparing teaching materials and adequate quality; control the discipline of students and prepare a supportive learning environment